Causes or Risk Factors of Cervical Cancer: Systematic Literature Review - Winancy Winancy; Herlia Sumardha Nasution; Ani Media Harumi; Novita Eka Kusuma; Siti Mar’atus Sholikah; Ni Gusti Made Ayu Agung Budhi (International Forum of Researchers and Lecturers, 2025)
Cervical cancer remains one of the leading causes of mortality among women, particularly in developing countries such as Indonesia, where prevalence is high and early detection is often delayed. This study aims to identify and synthesize the major risk factors for cervical cancer through a systematic review of both national and international literature. The core problem addressed is the lack of a comprehensive and context-relevant risk framework for Indonesian women, resulting in suboptimal preventive interventions. The proposed method is a qualitative descriptive literature review, analyzing 15 selected scientific articles based on defined inclusion criteria. Key findings indicate that age ≥35 years, high parity, early sexual activity, smoking habits, prolonged use of hormonal contraceptives, low educational attainment, and physically demanding occupations are significant determinants of increased cervical cancer risk. The synthesis of ideas shows that biological, behavioral, social, and environmental factors interact in complex ways to influence vulnerability to cervical cancer. This study concludes that cervical cancer prevention requires a multidimensional approach that integrates education, routine screening, and increased public awareness of modifiable risk factors. The findings are expected to inform more effective and context-sensitive health policy development in Indonesia.